1990
DOI: 10.1111/j.1151-2916.1990.tb05184.x
|View full text |Cite
|
Sign up to set email alerts
|

Order‐Disorder Phenomenon in Lead Scandium Tantalate

Abstract: Lead scandium tantalate (PST) is a ferroelectric relaxor with the perovskite structure of A(B'B)03. By suitable heat treatment, the B-site cations can be brought from a structurally disordered state into various degree of ordering. The degree of ordering is strongly affected by the amount of vacancies present in the materials. To suppress PhO loss during the sintering or annealing process, a PbO-rich atmosphere is supplied by materials having high PhO vapor pressure, such as PbZr03. For PST ceramics with nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…At low x ( x =0.00 and 0.05), the grain size is 1–3 μm, when x is greater than 0.05 ( x =0.10, 0.15, and 0.20), the grain size increases, with a scale of 4–6 μm. The sintering temperatures of PST and PbHfO 3 ceramics are 1560° and 1200°C, respectively 1,18 . While the PSTH( x ) ceramics are sintered by hot‐pressing at the same conditions (25 MPa, 1320°C, 2 h), then the low‐temperature sintering composition PbHfO 3 makes the grain size grow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At low x ( x =0.00 and 0.05), the grain size is 1–3 μm, when x is greater than 0.05 ( x =0.10, 0.15, and 0.20), the grain size increases, with a scale of 4–6 μm. The sintering temperatures of PST and PbHfO 3 ceramics are 1560° and 1200°C, respectively 1,18 . While the PSTH( x ) ceramics are sintered by hot‐pressing at the same conditions (25 MPa, 1320°C, 2 h), then the low‐temperature sintering composition PbHfO 3 makes the grain size grow.…”
Section: Resultsmentioning
confidence: 99%
“…L ead scandium tantalate (PbSc 0.5 Ta 0.5 O 3 , or PST) is a complex perovskite type of A(B′B″)O 3 , where B′ is a low‐valence cation and B″ is a high‐valence cation. The differences in the ionic radii and charge between the two B ions are sufficient to allow for an ordered structure 1–3 . Cross and colleagues demonstrated that the degree of B‐site order had a strong effect on the nature of the dielectric response, the peak permittivity, and phase transition temperature 4 .…”
Section: Introductionmentioning
confidence: 99%
“…L ead scandium tantalate (PbSc 0.5 Ta 0.5 O 3 , or PST) have attracted great research interest due to its order–disorder phenomenon in the past decades 1 . PST is a ferroelectric with the perovskite structure of A(B′B″)O 3 2 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, disordered compounds and solid solutions are known to undergo order-disorder phase transition [27][28][29][30] and, certainly, such transitions should exist in the relaxors. This problem has been studied soon after the discovery of the relaxors [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. It was shown that long high-temperature annealing of the simplest relaxors PSN and PST leads to the ordering with the cell doubling [32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%